1990
DOI: 10.1002/jnr.490260304
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor and K‐252a increase catecholamine release from PC12 cells

Abstract: PC12 cells are a nerve growth factor-responsive clone derived from a rat pheochromocytoma. The cells contain catecholamines and secrete them in response to depolarizing stimuli and cholinergic agonists. Treatment of the cells with nerve growth factor produces a number of very rapid changes, including the structural rearrangement of the cell membrane, the generation of a number of different second messengers, and the phosphorylation of several proteins. The present studies show that nerve growth factor treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
(20 reference statements)
0
24
0
Order By: Relevance
“…However, in those reports, the functional relevance of Ca 2ϩ mobilization after NGF stimulation was not clear. When functional studies were included, the authors related the Ca 2ϩ increases with the regulation of neurotransmitter release, and no correlation was established with ERK activation (76). Therefore, the results presented here indicate an additional and important role for the Ca 2ϩ increase after ligand-induced tyrosine kinase receptor stimulation (Trk or EGF receptor), since we demonstrate that intracellular Ca 2ϩ , through a CaM-dependent mechanism, is required for ERK-MAP kinase activation.…”
Section: Discussionmentioning
confidence: 57%
“…However, in those reports, the functional relevance of Ca 2ϩ mobilization after NGF stimulation was not clear. When functional studies were included, the authors related the Ca 2ϩ increases with the regulation of neurotransmitter release, and no correlation was established with ERK activation (76). Therefore, the results presented here indicate an additional and important role for the Ca 2ϩ increase after ligand-induced tyrosine kinase receptor stimulation (Trk or EGF receptor), since we demonstrate that intracellular Ca 2ϩ , through a CaM-dependent mechanism, is required for ERK-MAP kinase activation.…”
Section: Discussionmentioning
confidence: 57%
“…Previous experiments (30,35) have shown that K-252a alone mimics the actions of NGF on 45 Ca 2ϩ uptake, as it does on neurotransmitter release (46), in PC12 cells, and that uptake appears to be mediated by the p140 trk receptor (35). Treatment of 3T3-Trk cells with K-252a produced a marked increase in calcium levels in the cells (Fig.…”
Section: Resultsmentioning
confidence: 64%
“…One of the effects of NGF on PC12 cells is to induce catecholamine release, and this release is dependent upon the presence of extracellular calcium (46). By using an assay that measures the uptake of radioactive calcium into PC12 cells, it was further shown that NGF induced a small but rapid increase in the uptake of calcium (30).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the NGF-induced increases in calcium uptake in 3T3 cells have no biological relevance, the NGF receptors being introduced artificially. But increases of comparable magnitude in PC12 cells are absolutely required for the NGF-induced release of catecholamine neurotransmitters (28). Also there is a growing awareness that capacitative calcium entry plays a central role in many aspects of cell signaling (40), and the amounts of calcium entering the cells by this route appear to be very small indeed.…”
Section: Both P140mentioning
confidence: 99%
“…Indeed, it has been shown directly that NGF can stimulate a small, rapid increase in intracellular calcium concentration in PC12 cells (24 -26) and that this increase is accompanied by an NGF-induced increase in calcium uptake (27). Increased calcium uptake appears to be required for NGF-induced increases in neurotransmitter release (28). The molecular mechanism of NGF-induced calcium uptake is not well understood.…”
mentioning
confidence: 99%